1999
DOI: 10.1053/euhj.1998.1479
|View full text |Cite
|
Sign up to set email alerts
|

Extent, determinants and clinical importance of pressure recovery in patients with aortic valve stenosis

Abstract: This clinical study confirmed experimental data, that index pressure recovery is dependent on the ratio of the effective valve area and the cross-sectional area of the ascending aorta. Pressure recovery may need to be considered in patients with mild to moderate aortic stenosis and with a small cross-sectional area of the ascending aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 26 publications
4
34
1
1
Order By: Relevance
“…Our findings were in agreement with those of previous investigators (3,10,13), demonstrating that smaller AR dimension along with larger orifice areas increases the chance of reduced pressure gradients. Our results also demonstrate that jet eccentricity also plays an important role, increasing the pressure gradients at the orifice and limiting pressure recovery and therefore increasing functional severity in cases of bicuspid AS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings were in agreement with those of previous investigators (3,10,13), demonstrating that smaller AR dimension along with larger orifice areas increases the chance of reduced pressure gradients. Our results also demonstrate that jet eccentricity also plays an important role, increasing the pressure gradients at the orifice and limiting pressure recovery and therefore increasing functional severity in cases of bicuspid AS.…”
Section: Discussionsupporting
confidence: 93%
“…However, studies (7) have shown that in certain geometric situations (most commonly bileaflet mechanical prostheses), a significant amount of pressure loss is recovered distal to the valve orifice so that the Doppler-derived gradient overestimates the net pressure drop. It has been suggested that pressure recovery in AS depends on the ratio of the valve orifice area and the cross sectional area of the aorta, for this particular ratio determines the extent of flow separation and the formation of vortexes (4,10,13). Several researchers (1,9) have demonstrated that pressure recovery is more prominent in less severe AS, especially when the orifice area is Ͼ0.7 cm 2 .…”
mentioning
confidence: 99%
“…As expected from experimental data (1,2,17) and confirmed in small clinical studies (18 -20), the absolute magnitude of pressure recovery was greater in subjects with higher transvalvular velocities and more severe AS. However, the functional significance of pressure recovery was proportionately larger in patients with a lower degree of stenosis, confirming results in previous experimental and invasive studies (17,19).…”
Section: Discussionsupporting
confidence: 89%
“…PPM is a condition that occurs when the iEOA of a prosthetic valve is <0.85 cm/m 2 in the presence of elevated gradients across the prosthetic valve [25,26] and is severe at <0.65 cm/m 2 ; in other words, the prosthetic EOA is too small for the patient's BSA and hence his CO (Fig. 9.8).…”
Section: Prosthesis-patient Mismatch (Ppm)mentioning
confidence: 99%